Effect of carbon nanotubes functionalization on properties of their nanocomposites with polycarbonate/poly(acrylonitrile‐butadiene‐styrene) matrix. Issue 21 (18th January 2021) - Granada, Jonas E.; Maron, Guilherme K.; Beatrice, Cesar A. G.; Larocca, Nelson M.; Moreira, Eduardo C.; Alano, José H.; Pessan, Luiz A.; Santana, Ruth M. C.; Carreño, Neftali L. V.; de Oliveira, Amanda D.
Abstract: In this work, a comparative study evaluating the influence of different functionalization of carbon nanotubes on the properties of nanocomposites with polymeric matrix was performed. A 50/50 wt% polycarbonate (PC)/poly(acrylonitrile‐butadiene‐styrene) (ABS) blend was used as polymeric matrix of the nanocomposites. The comparison was made between nanocomposites reinforced with covalently functionalized multiwall carbon nanotubes (MWCNTf) and MWCNTf/nanoclay hybrid functionalization. The effect on the mechanical and morphological properties of the nanocomposites was evaluated through tensile and Izod impact tests and scanning electron microscopy and transmission electron microscopy (TEM) analyses. The thermal characterization of PC/ABS blends and nanocomposites was performed by differential scanning calorimetry (DSC). Results showed that both methods of functionalization of MWCNTs increased the stiffness and impact resistance of the nanocomposites. TEM micrographs indicated the preferred location of the reinforcements in the SAN phase of ABS. Results from DSC indicated an increase in the thermal resistance of the nanocomposites. Abstract : The purpose of this work was to develop nanocomposites materials consisting of PC/ABS matrix using functionalized multi‐walled carbon nanotubes (MWCNTf) as filler. The carbon nanotubes were modified by covalent and non‐covalent functionalization and then incorporated into the matrix. Results showed that both methods of functionalization of MWCNTs significantly improved the stiffness and impact resistance of the nanocomposites.